Encapsidation of DNA, a protein and a fluorophore into virus-like particles by the capsid protein of cucumber mosaic virus - Lu, Xiaoyun; Thompson, Jeremy R.; Perry, Keith L. (Journal of General Virology, 2012)
An important property of some spherical plant viruses is their ability to reassemble in vitro from native capsid protein (CP) and RNA into infectious virus-like particles (VLPs). Virions of cucumber mosaic virus (CMV) are stabilized by protein–RNA interactions and the nucleic acid is essential for assembly. This study demonstrated that VLPs will form in the presence of both ssDNA and dsDNA oligonucleotides, and with a lower size limit of 20 nt. Based on urea disruption assays, assembled VLPs from CMV CP and RNA (termed ReCMV) exhibited a level of stability similar to that of virions purified from plants, whilst VLPs from CMV CP and a 20mer exhibited comparable or greater stability. Fluorescent labelling of VLPs was achieved by the encapsidation of an Alexa Fluor 488-labelled 45mer oligonucleotide (ReCMV-Alexa488-45) and confirmed by transmission electron and confocal microscopy. Using ssDNA as a nucleating factor, encapsidation of fluorescently labelled streptavidin (53 kDa) conjugated to a biotinylated oligonucleotide was observed. The biological activity and stability of ReCMV and ReCMV-Alexa488-45 was confirmed in infectivity assays and insect vector feeding assays. This work demonstrates the utility of CMV CP as a protein cage for use in the growing repertoire of nanotechnological applications.